Efisiensi pemarasitan parasitoid Trichogramma chilotraeae nagaraja & nagarkatti (Hymenoptera:Trichogrammatidae) pada berbagai jumlah inang dan kepadatan parasitoid. - Hasriyanty Hasriyanty; Damayanti Buchori; Pudjianto Pudjianto (Perhimpunan Entomologi Indonesia, 2007)
The objective of the research was to study behaviour and parasitism efficiency of the egg parasitoid Trichogramma chilotraeae in relation to host and parasitoid density under laboratory condition. Eggs of Corcyra cephalonica were used as hosts for Trichogramma chilotraeae. Five different host (egg) densities: 3, 6, 12, 24 and 48 eggs were provided to one and two active female parasitoids T. chilotraeae. Percentage of parasitism, female progeny, and selfsuperparasitism were counted. Results showed that, host density was found to have a strong effect on parasitism rate, female progeny and selfsuperparasitism. Two parameters, parasitism and selfsuperparasitism decreases with increasing number of host density, in contrast, female progeny increase with increasing host density. Parasitoid density affected selfsuperparasitism and female progeny only on one level of host density (3 hosts) but not to all parameters of other density treatments.